2012
DOI: 10.1111/jph.12060
|View full text |Cite
|
Sign up to set email alerts
|

Minor Differences in Anther Extrusion Affect Resistance to Fusarium Head Blight in Wheat

Abstract: Fusarium head blight (FHB) remains a serious problem due to yield loss and mycotoxin accumulation in wheat production worldwide. We previously reported that the closed‐flowering (no anther extrusion) characteristic was effective for increasing resistance to FHB infection. In this study, we investigated the relationships between the degree of anther extrusion (AE) and FHB damage using double haploid lines (DHLs), derived from F1 plants from crosses between closed‐flowering and opened‐flowering varieties. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 30 publications
8
40
1
Order By: Relevance
“…This resistance is one of two major categories of resistance to FHB: resistance to initial infection (Type I), and resistance to pathogen spread in infected tissue (Type II) (Shroeder and Christensen 1963). Our results are in agreement with those of Kubo et al (2010Kubo et al ( , 2013 who found the severity of FHB infection in cleistogamous (closed flowering) recombinant inbred lines (RILs) and double haploid lines (DHLs) of wheat to be significantly lower than in chasmogamous (opened flowering) RILs and DHLs, hence demonstrating that the closed-flowering (no anther extrusion) characteristic was effective in increasing resistance to FHB infection. In their experiments, the lines set seed, hence seed set did not affect disease severity (as may have occurred in our experiments).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This resistance is one of two major categories of resistance to FHB: resistance to initial infection (Type I), and resistance to pathogen spread in infected tissue (Type II) (Shroeder and Christensen 1963). Our results are in agreement with those of Kubo et al (2010Kubo et al ( , 2013 who found the severity of FHB infection in cleistogamous (closed flowering) recombinant inbred lines (RILs) and double haploid lines (DHLs) of wheat to be significantly lower than in chasmogamous (opened flowering) RILs and DHLs, hence demonstrating that the closed-flowering (no anther extrusion) characteristic was effective in increasing resistance to FHB infection. In their experiments, the lines set seed, hence seed set did not affect disease severity (as may have occurred in our experiments).…”
Section: Discussionsupporting
confidence: 82%
“…The three lines all set seed, so the presence of seed may explain our results. The three fertile anther lines which set seed all had higher disease severity than the CMS lines which did not set seed, however, previous research by Kubo et al (2010Kubo et al ( , 2013 indicated seed setting did not affect disease severity. Seed setting alone may not fully explain our results.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Skinnes et al also demonstrated that even low anther extrusion is correlated with susceptibility to FHB infection 43 . Therefore, careful long-term observation from flowering to grain filling is required to select plants with complete cleistogamy 21 .…”
Section: Selection Of Line Integrating Type I and Ii Resistancementioning
confidence: 99%
“…This trait was not correlated to grain colonization or FHB resistance (results not shown). However, even little differences in anther extrusion can have a signifi cant impact on the susceptibility of the variety [17]. In a future investigation, the role of anthers on mycofl ora of grains has to be considered.…”
Section: Resultsmentioning
confidence: 99%